2016
DOI: 10.1080/09273948.2016.1192653
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescein Angiographic Findings in Patients with Active Systemic Lupus Erythematosus

Abstract: All patients with ocular lupus should be carefully evaluated for systemic involvement and, vice versa, all patients diagnosed with SLE should have a thorough ocular examination and FFA, even if they had normal fundus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
0
8
1
1
Order By: Relevance
“…Tolba et al emphasized the importance of performing a fundus fluorescein angiography (FFA) assessment in SLE patients. FFA detected retinal disease even in patients with normal fundus examination results [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tolba et al emphasized the importance of performing a fundus fluorescein angiography (FFA) assessment in SLE patients. FFA detected retinal disease even in patients with normal fundus examination results [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Typical findings of lupus retinopathy in the fluorescein angiography are tortuous retinal vessels, edema of papilla, hemorrhagic, or cotton-wool spots. One recent study has shown decreased survival in SLE patients with retinopathy compared to those without retinopathy, thus highlighting the importance of retinal diseases being both visually and prognostically [ 23 ]. The treatment of lupus retinopathy depends on the severity of disease, as visual outcome was usually better in those with cotton-wool spots than severe retinal vaso-occlusive disease [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with concurrent systemic diseases, including diabetes and/or hypertension, were not enrolled in the study. Complete history including the disease duration, activity score according to SLEDAI, 6 and treatment doses was documented. The study was approved by the Kasr Alainy Research Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%
“…One of these is the SLEDAI (SLE disease activity index), that is considered an important index for disease morbidity. 6 Enhanced depth imaging optical coherence tomography (EDI-OCT) is considered now the main noninvasive, rapid, objective, and reliable diagnostic technique for monitoring any choroidal changes. It allows in vivo examination and quantification of the choroid.…”
Section: Introductionmentioning
confidence: 99%